2014 IEEE 64th Electronic Components and Technology Conference (ECTC) 2014
DOI: 10.1109/ectc.2014.6897500
|View full text |Cite
|
Sign up to set email alerts
|

Improving the bond quality of copper wire bonds using a friction model approach

Abstract: In order to increase mechanical strength, heat dissipation and ampacity and to decrease failure through fatigue fracture, wedge copper wire bonding is being introduced as a standard interconnection method for mass production [1].To achieve the same process stability when using copper wire instead of aluminum wire a profound understanding of the bonding process is needed. Due to the higher hardness of copper compared to aluminum wire it is more difficult to approach the surfaces of wire and substrate to a level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Nevertheless, the contact status indicates a sticking area in the center of the touchdown interface. The region of maximum pressure and the status in the contact are confirmed by the microscopic analysis in [2]. There, it was found that the center region of separated bond connections was not fully bonded if low ultrasonic voltages and high bonding forces were used.…”
Section: Modeling Of Pre-deformationmentioning
confidence: 77%
See 1 more Smart Citation
“…Nevertheless, the contact status indicates a sticking area in the center of the touchdown interface. The region of maximum pressure and the status in the contact are confirmed by the microscopic analysis in [2]. There, it was found that the center region of separated bond connections was not fully bonded if low ultrasonic voltages and high bonding forces were used.…”
Section: Modeling Of Pre-deformationmentioning
confidence: 77%
“…Recent studies, e.g. [2], confirmed the strong impact of the pre-deformation process. There it was found that highly pre-deformed bonds adhere faster than less pre-deformed bonds while bonding on a soft DBC surface.…”
Section: Fig 1: Copper Wires Bonded Onto a Copper Substratementioning
confidence: 88%
“…By this it the simulation time could be reduced by more than a decade without losing significant accuracy. The ultrasonic transducer is modelled as a linear system as introduced in [10]. Fig.…”
Section: B Process Dynamicsmentioning
confidence: 99%